Structural levels of the national economic system: management aspect - G. N. Ryazanova; P. S. Tolkachev (Управление)
The organizational structure of the national economy, its internal levels (macro, meso and micro) has been analyzed in the article. The problems of the content of the concept of “economy”, segmented it into material and social components, have been identified. Attention has been focused on the negative aspects of the globalization of the world economy, based on the main provisions of the neoclassical paradigm. It has been noted, that to ensure the socio-economic integrity of the national economy, it is necessary to transform the generic state of society into a centrally-organized.According to the authors, to implement the transformation of the socio-economic space into an integrated socioeconomic system, it is necessary to coordinate three hierarchically subordinate levels: macro, meso, and microeconomic agents. The macroeconomic agent forms subject relations between all hierarchical levels, which require a high level of government: it cannot be a command economy, since this strategy of economic development paralyzes competition and free enterprise, but there can be no purely market economy, because the “invisible hand of the market” unable to ensure sustainable harmonious development of the economy without government intervention.It has been concluded about the need for an integrated nature of management of the Russian economy and the tasks for improving the system of management of the Russian economy have been determined. It is emphasized, that at the present stage, the greatest attention should be paid to the issues of improving the management of the mesostructure of the Russian economy – the development of industries and regions, since at the moment this level of the economy is paid fragmentary attention. The analysis has been carried out using general scientific methods: the method of abstraction, historical research methods; formalization method, reconstruction method; based on a systematic approach using the method of forecasting.